Interictal stereo-electroencephalography features below 45 Hz are sufficient for correct localization of the epileptogenic zone and postsurgical outcome prediction - Klimes, Petr; Nejedly, Petr; Hrtonova, Valentina; Cimbalnik, Jan; Travnicek, Vojtech; Pail, Martin; Peter-Derex, Laure; Hall, Jeffery; Pana, Raluca; Halamek, Josef; Jurak, Pavel; Brazdil, Milan; et al. (Epilepsia, 2024)
OBJECTIVE: Evidence suggests that the most promising results in interictal localization of the epileptogenic zone (EZ) are achieved by a combination of multiple stereo-electroencephalography (SEEG) biomarkers in machine learning models. These biomarkers usually include SEEG features calculated in standard frequency bands, but also high-frequency (HF) bands. Unfortunately, HF features require extra effort to record, store, and process. Here we investigate the added value of these HF features for EZ localization and postsurgical outcome prediction. METHODS: In 50 patients we analyzed 30 min of SEEG recorded during non-rapid eye movement sleep and tested a logistic regression model with three different sets of features. The first model used broadband features (1-500 Hz); the second model used low-frequency features up to 45 Hz; and the third model used HF features above 65 Hz. The EZ localization by each model was evaluated by various metrics including the area under the precision-recall curve (AUPRC) and the positive predictive value (PPV). The differences between the models were tested by the Wilcoxon signed-rank tests and Cliff's Delta effect size. The differences in outcome predictions based on PPV values were further tested by the McNemar test. RESULTS: The AUPRC score of the random chance classifier was .098. The models (broad-band, low-frequency, high-frequency) achieved median AUPRCs of .608, .582, and .522, respectively, and correctly predicted outcomes in 38, 38, and 33 patients. There were no statistically significant differences in AUPRC or any other metric between the three models. Adding HF features to the model did not have any additional contribution. SIGNIFICANCE: Low-frequency features are sufficient for correct localization of the EZ and outcome prediction with no additional value when considering HF features. This finding allows significant simplification of the feature calculation process and opens the possibility of using these models in SEEG recordings with lower sampling rates, as commonly performed in clinical routines.
Keywords: výsledek terapie; Young Adult; Electroencephalography; Male; EEG; mladý dospělý; Adolescent; stereotaktické techniky; Child; epilepsy; elektroencefalografie; dítě; Adult; dospělí; mužské pohlaví; interictal epileptoform discharges; epilepsie; mladiství; Stereotaxic Techniques; Treatment Outcome; lidé; high‐frequency oscillations; ženské pohlaví; Humans; Drug Resistant Epilepsy; refrakterní epilepsie; Epilepsy; Female; lidé středního věku; machine learning; Middle Aged